Epidemiological overlaps in COVID-19 and malaria within healthcare and community settings of Southern Ghana - Amegatcher, Gloria; Acquah, Maame E.; Tetteh, Deborah K.; Obeng, Rachael; Debrah, Ethel; Quist, Bridget; Acquah-Jackson, Priscilla; Boateng, Kyerewaa A.; Twieku, Gideon; Armoo, Samuel; Awandare, Gordon A.; Mosi, Lydia; et al. (Frontiers in Public Health, 2024)
Background COVID-19 disruptions including lockdowns and prioritization of COVID-19 control programs in Africa in 2020–2022 contributed to reductions in malaria control activities including malaria diagnosis, treatment and resistance monitoring. This study investigated the malaria burden and distribution on the background of active transmission of SARS-CoV-2 in Southern Ghana; utilizing community health education and medical screening (CHEMS) approach to determine epidemiological overlaps in COVID-19 and malaria. Methods Between October–December 2022, prospective cross-sectional surveys, with CHEMS were conducted in Greater Accra and Central regions, where 994 participants enrolled either at a hospital or community setting provided demographic and clinical data including history of clinical malaria infection and antimalarial treatment in the past 2 weeks. Of this study population, 953 provided nasal/throat swabs for COVID-19 RT-PCR testing, with a subset of 136 participants also providing finger-prick blood for malaria RDT testing. Results The study population comprised of 73.6% adults, with 54.6% COVID-19 vaccination rate. Overall, 18.1% of participants had a history of clinical malaria, which was associated (adjusted odds ratio > 1.50, p-value ≤0.022) with COVID-19 symptoms and positivity, study area and hospital setting, suggestive of overlaps in the epidemiological risk for malaria. On a background of widespread SARS-CoV-2 infections (12–37%), malaria parasitaemia was detected in 6%, with 2% being co-infections with SARS-CoV-2. Among the malaria positives, 9.5% had a history of antimalarial treatment, which suggested that their infections were recrudescent parasitaemia. Conclusion The epidemiological and clinical overlap between malaria and COVID-19 within the hospital and community settings underscores the need for accurate case diagnosis to inform effective clinical treatments. Innovative surveillance programs, with community engagement are needed to maximize control interventions including treatment of asymptomatic malaria infections.